"Childless? Childfree? Neither, Just ME": pronatalism and (m)otherhood in Paula Knight's The Facts of Life. Issue 2 (4th March 2021) - Venkatesan, Sathyaraj; Murali, Chinmay
ABSTRACT: Defining female identity primarily in terms of their childbearing capacity is prevalent across cultures. Centrality of motherhood within discursive formations of womanhood has resulted in establishing inextricable linkages between maternity and femininity. The reproductive ethic privileged by sociocultural discourses and institutions, which are impelled by the pervasive ideology of pronatalism, coerces women to procreate, reducing their identity to mere reproducing bodies. Consequently, those who are unable to reproduce due to fertility-related disorders encounter severe cultural derision and social stigmatisation. Paula Knight's autopathography The Facts of Life is a harrowing account of the author's struggles with infertility in a pronatal society. In a close reading of Knight's graphic memoir, this article aims to investigate how the pluripotent space of the comics medium allows the author to arraign the ideology of pronatalism as an oppressive force that mediates her lived experience of infertility. Drawing theoretical insights from Ellen Peck, Judith Senderowitz, and Louis Althusser, among others, the essay also seeks to examine the socially constructed and gendered nature of (m)otherhood as it unfolds in Knight's narrative.